Lift structural plan and design for Kolej Kediaman Tiga Universiti Malaysia Pahang - Siti Norashikin, Yusoff (2013)
In Malaysia, the lift will normally be built in the building that has five or more than five floors. Kolej KediamanTiga of Universiti Malaysia Pahang that are here are just four floors, the norm on new student registration will normally be delivery problems arise if the student can be placed in high benchmark suite. The main focus is the design of building lifts. In the design of this lift, one part to consider is the for machine room slab. Where machine room slab must be designed to carry the load right. After the need to design an appropriate wall to and also to design a suitable type of foundation based on the type of soil and the burden borne by the elevator building. All these structures are designed and analyzed using the Esteem software.